Dampak Program Pelatihan Afiliasi terhadap Peningkatan Kompetensi Pemasaran UMKM di Kelurahan Jrebeng Kulon - Abdul Jalal; Achmad Farishy Firmansyah; Muhamad Arif; Uswatun Hasanah; M. Jadid Khadavi (Pusat Riset dan Inovasi Nasional, 2026)
This community service activity was carried out to assist MSME (Micro, Small, and Medium Enterprises) actors in Jrebeng Kulon Village in understanding and utilizing affiliate programs as a digital marketing strategy. The training was conducted through material presentation, demonstrations, and practical mentoring to ensure participants could follow each step more easily. Before the training, most participants were unfamiliar with the concept of affiliation and lacked the technical skills to use affiliate platforms. After participating in the activity, a significant increase was observed, particularly in the participants' ability to create accounts, select products, understand the commission system, and embed affiliate links. This change indicates that a practice-based training method is effective in helping MSMEs adapt to the developments in digital marketing technology. Overall, this training provided tangible benefits in improving digital literacy and opening opportunities for MSMEs to grow their businesses through a more effective and relevant marketing strategy in the digital era.